CD24, CD27, CD36 and CD302 gene expression for outcome prediction in patients with multiple myeloma - Alaterre, Elina; Goldschmidt, Hartmut; Seckinger, Anja; Hose, Dirk (OncoTarget, 2017)
Multiple myeloma (MM) is a B cell neoplasia characterized by clonal plasma cell (PC) proliferation. Minimal residual disease monitoring by multi-parameter flow cytometry is a powerful tool for predicting treatment efficacy and MM outcome. In this study, we compared CD antigens expression between normal and malignant plasma cells to identify new potential markers to discriminate normal from malignant plasma cells, new potential therapeutic targets for monoclonal-based treatments and new prognostic factors. Nine genes were significantly overexpressed and 16 were significantly downregulated in MMC compared with BMPC (ratio ≥2; FDR CD24, CD27, CD36 and CD302) was associated with a prognostic value in two independent cohorts of patients with MM (HM cohort and TT2 cohort, n=345). The expression level of these four genes was then used to develop a CD gene risk score that classified patients in two groups with different survival (P = 2.06E-6) in the HM training cohort. The prognostic value of the CD gene risk score was validated in two independent cohorts of patients with MM (TT2 cohort and HOVON65/GMMGHD4 cohort, n=282 patients). The CD gene risk score remained a prognostic factor that separated patients in two groups with significantly different overall survival also when using publicly available data from a cohort of relapsing patients treated with bortezomib (n=188). In conclusion, the CD gene risk score allows identifying high risk patients with MM based on CD24, CD27, CD36 and CD302 expression and could represent a powerful tool for simple outcome prediction in MM.
Gesehen am 12.04.2018